TESTING THE FIRM VALUE LISTED IN THE INDONESIAN SHARIA STOCK INDEX DURING THE COVID-19 PANDEMIC - Awliya, Aldy; Bertuah, Eka (BAKI (Berkala Akuntansi dan Keuangan Indonesia), 2023)
This study aims to test the firm value registered ISSI during the Covid-19 pandemic. The data is financial reports. Cross sectional data type. Data were analyzed using the Multiple Linear Regression Analysis technique and Moderation Regression Analysis in 2020 and different tests on financial reports in quarters II,III,IV before the 2019 pandemic and quarters II,III,IV the 2020 pandemic. Sample used purposive sampling in ISSI. The results the research are through multiple linear regression testing and testing the moderating variable, liquidity does not have an impact on value, size does not strengthen the correlation liquidity on value, leverage has an influence on value, size strengthens the impact leverage on value. Profitability has a positive influence on value, size impacts profitability on value. Activity has no effect on value, size does not strengthen the impact activity on value. Dividend policy has no effect on value, size does not strengthen the impact dividend policy on value. The results the different value tests show that there were differences in values pre-pandemic and pandemic for the non-primary consumer, primary consumer, energy, infrastructure, and health. The raw materials, finance, industry, property & real estate, technology, transportation & logistics had no difference in value pre-pandemic or pandemic.